Interaction as a Pedagogical Category - Androshchuk, Iryna (Pedagogical Discourse, 2013)
The article analyzes the main approaches to the concepts of «interaction» and «pedagogical interaction». Based on generalization approaches in psychological and pedagogical literature of scholars, researchers, the essence of the notion «pedagogical interaction» is clarified, and the main features and deployment mechanisms of pedagogical interaction are found out. The emphasis is on the subjects of pedagogical interaction in the process of training of the future specialists. Attention is focused on the problems that arise during teaching interactions. The scheme proved that the implementation of professional training will be more effective in case of establishing of pedagogical interaction between the subjects of the educational process in all its manifestations.